EFFICACY OF PREBIOTIC DOSE OF LACTULOSE IN FUNCTIONAL NUTRITION OF INFANTS WITH ENTEROCOLITIS AND INTESTINAL DISBIOSIS - Ye.R. Meskina; Е.V. Trofimenko ("Paediatrician" Publishers LLC, 2011)
The article presents a data from a clinical study describing different clinical effects of lactulose. The direction of drug's efficacy depends on different dose of lactulose. The use of prebiotic dose (milk mixture «Bifidus 1, 2») improves the state of intestinal micro flora, favors to the increase of efficacy of usually used treatment and decreases the probability of unfavorable rehabilitation period in infants with infectious enterocolitis and intestinal disbiosis.Key words: infants, infectious enterocolitis, intestinal micro flora, short-chain fatty acids, lactulose.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 105-110)